EKSPRESI RESEPTOR VITAMIN D PADA LESI DAN PERILESI KULIT PASIEN VITILIGO BERDASARKAN PEMERIKSAAN (Perhimpunan Dokter Spesialis Kulit dan Kelamin Indonesia (PERDOSKI), 2023)
Abstract Introduction: Vitamin D is known to have many functions in the body, one of them is acts as an immunomodulator. This vitamin works through gene transcription of certain cells that express vitamin D receptors (VDR). Objective: To more understand the role of vitamin D in vitiligo based on RVD. Methods: This study using observational analytic study with cross-sectional method. The case group consisted of vitiligo patients whose skin was taken from the lesion area and perilesion through a plong biopsy procedure and stored as stored biologic material, while the control group were burn patients and chronic wounds from Plastic Surgery Outpatient, that underwent a split-thickness skin graft from the healthy skin. RVD expressions were examined by immunohistochemical using monoclonal antibodies and assessed by two reviewers. Results: The results showed that the mean VDR histoscore in the skin lesions of vitiligo (4.96 ± 1,852) was higher than controls (2.47 ± 0.405). The mean skin perilesion of vitiligo (5.07 ± 1,321) was higher than controls (2.47 ± 0.405). The mean histoscore of lesion was higher (4.96 ± 1,852) but was not statistically significant compared to perilesion vitiligo (5.07 ± 1,321). Conclusion: The expressions of RVD in perilesion vitiligo patients are lower than lesion. However, RVD expression of vitiligo patient was not lower than control group. This result shows that RVD plays little role in pathogenesis of vitiligo.